Utilization of Pavement Condition Index on Runway Pavement Sultan Babullah Ternate Airport - Sabaruddin; M Taufik YS; Rizky KS (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The Pavement Condition Index (PCI) assessment is one method used to assess the state of airport runway pavement. The runway (flexible pavement) of Sultan Babullah Ternate Airport, which has a size of 2300 m by 45 m, served as the site for PCI research in this study. The ASTM D5340-12 procedure (Standard Test Method For Airport Pavement Condition Index Surveys) was used to examine this PCI. The average PCI value of the entire sample was calculated from the results of the overall PCI study by averaging all PCI values for each sample, the results for the average PCI value of the entire sample were obtained at 60 (medium). Damage to STA 0+700 is on a bad scale with a PCI calculated value of 41, Damage to STA 0+750 is on a bad scale with a PCI calculated value of 41, Damage to STA 0+850 is on a bad scale with the value of the PCI calculation result is 31, Damage to STA 0+900 is on a bad scale with a PCI calculation result value of 36, Damage to STA 0+950 is on a bad scale with a PCI calculation result value of 34, Damage to STA 1+1050 is on a bad scale with a PCI calculation result value of 59.